Applications of ionic liquids in starch chemistry: a review. Issue 7 (14th February 2020) - Ren, Fei; Wang, Jinwei; Xie, Fengwei; Zan, Ke; Wang, Shuo; Wang, Shujun
Abstract : Recently, the use of ionic liquids as promising "green solvents" in starch chemistry has gained extensive interest, especially in the areas of chemical modification of starch and the development of starch-based materials. Abstract : Recently, the utilization of starch to replace synthetic polymers for the manufacture of green materials has gained extensive interest, due to its renewability, biodegradability, abundance and low cost. On the other hand, ionic liquids (ILs) have been widely recognized as promising "green solvents" to replace volatile organic solvents for polysaccharide processing. Over the past few years, ILs have been increasingly demonstrated to serve as excellent media for the dissolution, plasticization and derivatization of starch. This allows the synthesis of chemically modified starches with high degree of substitution (DS) and the development of various starch-based materials such as thermoplastic starch, composite films, solid polymer electrolytes, nanoparticles and drug carriers. The main objective of this review is to present an overview of the roles of ILs in starch dissolution, gelatinization, modification and plasticization, and their industrial applications. Moreover, this review is intended to provide a comprehensive understanding of the mechanisms behind the IL-processing of starch and to provide insights into the rational development of novel starch-based materials with ILs.